Intention to Purchase Luxury Products: Risk Issues in Online Shopping - Kevin, Pascalis; Hendrawan, Ranny Marcella; Widjojo, Handyanto; Wibowo, Alexander Joseph Ibnu (Journal of Marketing Innovation (JMI), 2024)
Online retailers face significant challenges due to the intangible nature of virtual shopping, which particularly affects the luxury goods sector. This study investigates how website quality, perceived risk, money-back guarantees, quality labels, and risk-taking tendencies influence consumers' intentions to purchase luxury goods online. Data were collected by distributing survey questionnaires online. Data from 249 questionnaires were obtained using a nonprobability sampling technique. Respondents were users of a luxury product website in Indonesia. Furthermore, eight hypotheses were tested using covariance-based structural equation modeling (CB-SEM) with the AMOS 26 application. This study yielded four main findings: (i) quality labels, money-back guarantees, website quality, and risk-taking were shown to directly influence consumers' perceived risk; (ii) website quality is the dimension that most strongly influences consumers' perceived risk; (iii) money-back guarantees and website quality do not directly influence online shopping intentions; and (iv) consumer-perceived quality and risk labels have been shown to directly influence consumers' intention to buy luxury brands online. This research provides valuable insights by focusing on an emerging market and highlights that risk-taking tendencies directly affect perceived risk, with website quality being the most substantial determinant of perceived risk among luxury consumers.